Virtual mode in a discipline in the Medicine career in times of pandemic: students' perception - Victor Olegario Giayetto; María Gabriela Peirotti; Claudia Beatriz Ramona Aimaretto; Marcos Agustín Vera (Universitat Politècnica de València, 2020)
COVID-19 has broken into the lives of the world's citizens, forcing to quarantine. Higher Education was no stranger to this phenomenon. The face-to-face became virtual. Students' vision is important in this setting. An observational, descriptive, quantitative and qualitative study was carried out for Microbiology and Parasitology students from the Medicine career at the National University of Villa María, Córdoba province; Argentina; in order to know their opinion regarding this drastic move and to know about the perceived difficulties. The main obstacles were: 24.2% overload of activities, 16.5% lack of contact with teachers, 13.2% not being clear on the course objectives; 4.4% lack of time, 3.3% fear of failure, 3.3% absence of practical classes, 2.2% working and studying at the same time. The positive aspects of this modality were: 37.83% availability of time to organize, organize and study at their own pace; 32.43% delivery of teachers and organization of the Institution in the face of this crisis; 10,81% recorded theoretical classes are a good tool to prove; 9.45% highlighted behavioral changes, learning new tools to study and 6.75% self-learning. 12.16% did not rescue any positive aspect. It is important to diagnose the perception of the students in this context to avoid difficulties when designing and accrediting such curricular spaces.